Naggy Aunt Aggy - Norton, Liss (Wayland London, 2011)
"When Aunt Aggie came to stay at Creepy Castle, Skelly Nelly and Bony Tony were not happy! She made them scrub the floors and sweep away the cobwebs. When she told them to clean the bath, it was time to get ride of Naggy Aunt Aggie!"--Back cover